Dostoevsky’s Poetics of Modern Freedom: Against Bakhtin’s "Polyphonic" Moral Truth - Wright, Ava (Labyrinth, 2021)
In an influential treatise, Mikhail Bakhtin (1984) asserts that the aim of Dostoevsky's distinctive poetics is to advance a revolutionary, "polyphonic" model of moral truth. In this paper, I argue that while Bakhtin correctly identifies essential features of Dostoevsky's poetics, these features are better understood as oriented toward meeting the free modern individual's need to test ultimate moral ends and concomitant virtues in order to determine their truth. An Aristotelian poetics intended to educate audiences only in how to be virtuous to achieve moral ends that are given by tradition will have different essential features than will a modern poetics whose purpose is to help individuals determine what the virtues are. It is this latter purpose, I argue, that drives Dostoevsky to create the new stylistic devices that Bakhtin observes in Dostoevsky's work, rather than the purpose of realizing a philosophically problematic "polyphonic" model of moral truth.